Nineteen minutes - Picoult, Jodi, 1966- (London : Hodder & Stoughton Ltd, 2007)
"In Sterling, New Hampshire, 17-year-old high school student Peter Houghton has endured years of verbal and physical abuse at the hands of classmates. His best friend, Josie Cormier, succumbed to peer pressure and now hangs out with the popular crowd that often instigates the harassment. One final incident of bullying sends Peter over the edge and leads him to commit an act of violence that forever changes the lives of Sterling's residents"--Author's website
Keywords: Bullying -- Fiction; School shootings -- New Hampshire -- Fiction; Witnesses -- New Hampshire -- Fiction; Mystery fiction